Antibacterial activity and Mimosa caesalpiniaefolia extract nonstick Benth on dental biofilm microorganisms / Atividade antibacteriana e antiaderente do extrato de Mimosa caesalpiniaefolia Benth sobre micro-organismos do biofilme dentário - Felipe Henrique de Souza Lima; Gustavo Shilmaney Damasceno; Luana Luzia Santos Pires; João Gomes da Costa; Thiago José Matos Rocha; Aldenir Feitosa dos Santos (Universidade Estadual de Alagoas, 2018)
Dental caries and periodontal diseases are the two common threats to oral health and important public health problems because of your impact on individuals. S. mutans is considered the main Etiologic Agent of dental caries in humans. Eradication of biofilm is a difficult task. Facing the limitations of mechanical methods of hygiene. This work aimed to evaluate the antibacterial activity and Mimosa caesalpiniaefolia extract nonstick Benth on dental biofilm microorganisms. It is an analytical study in vitro trial. The screening test and the CIM were analyzed by the method of microdiluição in broth. The lines cariogênicas and dental biofilm-forming analyzed were Streptococcus mitis ATCC ATCC 25175 9811, Streptococcus mutans, Streptococcus sanguis ATCC 10557, Streptococcus sobrinus 27609 and Lactobacillus casei ATCC ATCC 7469. It has been seen that in during the antibacterial activity of the extract of the leaves of Mimosa caesalpinifolia on cariogênicas lines and formed of dental biofilm that the species studied showed minimum inhibitory concentration and minimum bactericidal Concentration about Streptococcus mutans ATCC 25175 and Streptococcus mitis ATCC 9811. The ethanolic extract of leaves of Mimosa caesalpinifolia presented significant antimicrobial action and minimum inhibitory activity